Analisis Majas Hiperbola dalam Lirik Lagu This Is Me Pada soundtrack film berjudul The Greatest Showman - Aji Jehan Fellani (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2022)
In a literary work, especially poetry or song lyrics, figure of speech is very common to appear so that the poem or song lyrics become more beautiful. One of the figures of speech that is often used is hyperbole. This figure of speech serves to give a great impression by exaggerating sentences. The lyrics of the song, This Is Me, which is the original sound tract from the film The Greatest Showman, is very thick with the use of hyperbole figure of speech. This is because the moral message of the song is to inspire the listeners.